2006
DOI: 10.1123/rsj.30.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Attributes, and Competencies Sought in New Hires by Campus Recreation Directors

Abstract: Professionals and students working in college recreation departments are often involved in many facets relating to the hiring of competent employees. A review of literature revealed that various professions sought different qualities in potential job candidates. There were few examples of research relating to the qualities sought by potential employers of campus recreation personnel. Therefore, recreation directors, holding a NIRSA institutional membership, were surveyed to determine the characteristics, attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Certifications specific to outdoor recreation enable COR staff to maintain updated skill sets in their areas of specialized knowledge. Successful completion of certification courses and skill-based trainings make COR staff more marketable during the hiring process when seeking jobs within their field (Schneider et al, 2006).…”
Section: Researchmentioning
confidence: 99%
“…Certifications specific to outdoor recreation enable COR staff to maintain updated skill sets in their areas of specialized knowledge. Successful completion of certification courses and skill-based trainings make COR staff more marketable during the hiring process when seeking jobs within their field (Schneider et al, 2006).…”
Section: Researchmentioning
confidence: 99%
“…A semistructured interview guide based on the previous literature in campus recreation hiring practices (cf., Steir Jr. et al, 2006), preferred job competencies (cf., Ball et al, 2008;Schneider et al, 2006), and successful career path factors (Ross & Schurger, 2007) was developed. The basic elements of the literature were used to develop the interview guide.…”
Section: Instrumentmentioning
confidence: 99%
“…The study participants indicated commitment and integrity, communication skills, ability to manage a budget, personnel management, and adaptability to change were the traits campus recreation directors should possess. In another study exploring job competencies, Schneider, Steir Jr., Kampf, Haines, and Wilding (2006), collected data from 241 NIRSA professionals. Consistent with previous research, Schneider et al, found that campus recreation directors expected new hires to have excellent communication skills (oral and written) and have direct job-related experience in a variety of campus recreation settings.…”
mentioning
confidence: 99%
“…This study reinforced the belief that recreational sports programmers needed competencies in a variety of areas related to business, theory, and programming. Schneider, Stier, Kampf, Haines, and Wilding (2006) looked at competencies in campus recreation in a different way. Instead of examining competencies of current employees, they identified competencies sought in new hires by campus recreation directors for entry-level positions (undergraduate students, graduate students, and professional positions).…”
mentioning
confidence: 99%